Effect of gargling with green tea (Camellia sinensis) brewing on plaque index score of fixed orthodontic users of dental students of Baiturrahmah University: Efek berkumur dengan seduhan teh hijau (Camellia sinensis) terhadap skor indeks plak pengguna ortodonti cekat mahasiswa kedokteran gigi Universitas Baiturrahmah - Warani, Parastia; Kornialia; Orienty, Fauzia Nilam; Alamsyah, Yenita; Amly, Dina Auliya (Makassar Dental Journal PDGI Makassar, 2025)
Treatment with fixed orthodontic appliances can pose various risks, especially increasing plaque accumulation. Green tea (Ca-mellia sinensis) which is one of the natural alternatives that can be used to inhibit dental plaque formation, contains catechins, flavonoids and tannins as antibacterial Streptococcus mutans which is the agent of dental plaque formation. This article discus-ses the difference in orthodontic plaque index (OPI) scores before and after rinsing with green tea brewing (GTB) in fixed ortho-dontic users. Experimental research with a one-group pretest-posttest design using research subjects namely preclinical stu-dents of Baiturrahmah University Faculty of Dentistry class 2022 and 2023 who used fixed orthodontics according to the inclu-sion criteria totalling 40 people. Data collection according to the examination of OPI score before and after gargling with GTB. Data analysis showed a significance value of p=0.000 (p<0.05) which indicated that there was a difference in OPI scores be-fore and after gargling, which decreased from 41.75% to 23.94%. It was concluded that gargling with GTB can reduce the OPI score of fixed orthodontic users.